Core‐shell nanocatalysts with reduced platinum content toward more cost‐effective proton exchange membrane fuel cells. Issue 11 (26th August 2022) - Li, Qun; Zhang, Guisheng; Yuan, Botao; Zhong, Shijie; Ji, Yuanpeng; Liu, Yuanpeng; Wu, Xiaoqiang; Kong, Qingquan; Han, Jiecai; He, Weidong
Abstract: Proton exchange membrane fuel cells (PEMFCs) have become a major component of current clean energy technologies. Accounting for nearly half the cost of a commercial fuel cell stack, Pt‐based catalysts are the main choices for both anode and cathode in PEMFCs. However, catalytical activity and operating life of Pt‐based catalysts are still unsatisfactory. High cost and scarcity of Pt further hinder the development of PEMFCs. Constructing core‐shell structure for Pt‐based catalysts is a promising strategy to enhance the catalytic activity and reduce the cost. In this review, we overview recent advances in Pt‐based core‐shell catalysts according to catalytic reaction types involved in PEMFCs. Furthermore, we discuss the working principle of core‐shell catalysts from the perspective of coupling between core and shell. In the end, we conclude the recent progress and discuss the future developments and facing challenges. Abstract : Pt‐based catalysts are the main choices for both anode and cathode in PEMFCs. Constructing a core‐shell structure for Pt‐based catalysts is a promising strategy to enhance the catalytic activity and reduce the cost. This review overviews recent advances in Pt‐based core‐shell catalysts in PEMFCs, displays the working principle of core‐shell catalysts, and discusses future developments and facing challenges.